Nanoparticle-Based Sustainable Agriculture and Food Science: Recent Advances and Future Outlook - Mittal, Deepti; Kaur, Gurjeet; Singh, Parul; Yadav, Karmveer; Ali, Syed Azmal (Frontiers in Nanotechnology, 2020)
In the current scenario, it is an urgent requirement to satisfy the nutritional demands of the rapidly growing global population. Using conventional farming, nearly one-third of the crops get damaged mainly due to pest infestation, microbial attacks, natural disasters, poor soil quality, and lesser nutrient availability. More innovative technologies are immediately required to overcome these issues. In this regard, nanotechnology has contributed to the agrotechnological revolution that has imminent potential to reform the resilient agricultural system, while promising food security. Therefore, nanoparticles are becoming a new-age material to transform modern agricultural practices. The variety of nanoparticles-based formulations, including, nano-sized pesticides, herbicides, fungicides, fertilizers, and sensors, have been widely investigated for plant health management and soil improvement. In-depth understanding of plant and nanomaterial interactions opens new avenues towards improving crop practices through increased properties like disease resistance, crop yield, and nutrient utilization. In this review, we highlight the critical points to address the current nanotechnology-based agricultural research that could benefit productivity and food security in future.